Comparison of three instruments to assess changes of motor impairment in acute hemispheric stroke: the Stroke Impairment Assessment Set (SIAS), the National Institute of Health Stroke Scale (NIHSS) and the Canadian Neurological Scale (CNS). (August 2014) - Seki, Masaru; Hase, Kimitaka; Takahashi, Hidetoshi; Liu, Meigen
Abstract Purpose: The purpose was to compare the performance of three representative instruments to measure changes of motor recovery with acute hemispheric stroke. Method: In 41 consecutive patients with acute hemispheric infarction, motor recovery was assessed within 3 days of onset and then every 2 weeks until the 12th week with the Stroke Impairment Assessment Set (SIAS), the National Institutes of Health stroke scale (NIHSS) and the Canadian Neurological Scale (CNS). We analyzed the relationships among the corresponding subscales of the three instruments with the Spearman's rank correlation method, and compared their responsiveness by plotting the temporal profiles of scores of each instrument and by testing the significance of changes over time with the Friedman test. Results: High correlations were observed among the three instruments at each examination point. However, the SIAS scores were more widely dispersed at the same NIHSS and CNS scores. Friedman test revealed that the scores changed significantly during the observation period with the SIAS and the CNS but not with the NIHSS. The changes were detected later with the CNS than with the SIAS. Conclusions: Although the assessment results with the three instruments were highly inter-correlated, the SIAS performed better with respect to responsiveness to changes. Implication for Rehabilitation When providing rehabilitation services to patients with stroke, it is important to document objectively the level of their impairment from the acute stage and during the entire course of rehabilitation with standardized instrument, and to predict their functional outcomes as early and accurately as possible. This study therefore compared three representative instruments with established psychometric properties, the SIAS, the NIHSS and the CNS, with respect to their ability to document motor impairment and their responsiveness to recovery in patients with acute hemispheric stroke.